IMPLEMENTATION OF VILLAGE FUND MANAGEMENT POLICIES IN 2022 TO IMPROVE THE ECONOMY OF THE KALIWINING VILLAGE COMMUNITY RAMBIPUJI JEMBER - Fauziyah, Ria; Wahyudi, Edy; Handini, Yuslinda Dwi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
After the enactment of the Law on Villages No. 6 of 2014, villages have their own authority in making regulations or village-scale local authority. In addition, the state also provides funds to villages through transfers regulated in Government Regulation No. 60 of 2014 as a form of effort to equalize and accelerate development in the village. Meanwhile, the implementation of fund management in the village uses regulatory guidelines from the Ministry of Villages that adjust to national conditions. National economic recovery is the most important part after declaring Indonesia free from the Covid-19 pandemic and continues through SDG-based activity programs to improve the population's economy. This research uses a qualitative descriptive method by referring to the policy implementation theory of Donald Van Meter and Carel Van Horn. Village financial management cannot be separated from the policy of the village head as the PKPKD (Village Financial Management Power Holder) although in general the use of village funds can only be allocated for the administration of village government, development, community development, community empowerment and emergency disaster management.